Meta-analysis of peer-reviewed agricultural research data from Africa - Rosenstock, Todd S.; Steward, Peter Richard; Lamanna, Christine (2022)
The ERAg r-package provides access to the ERA dataset, bibliographic information, associated biophysical data, analytical functions and vignettes. See the package vignettes for how to use the package and access the data contained within. Version: 0.0.1.0000 Evidence for Resilient Agriculture (ERA) was principally supported by CGIAR Consortium Research Program on Climate Change, Agriculture and Food Security (CCAFS) Flagship on Climate-Smart Practices and Technologies (FP2) under the Partnerships for Scaling Climate-Smart Agriculture (P4S) Project (Phase I: P159, Phase II: P1593). Supplemental support was provided by European Union-International Fund for Agricultural Development (EU-IFAD) as part of the Building Livelihoods and Resilience to Climate Change in East and West Africa project (CIAT: C-102-19); Food and Agriculture Organization of the United Nations (FAO); United States Department of Agriculture Foreign Agricultural Service project Operationalizing Climate-Smart Agriculture in Kenya and Malawi (USDA-FAS: FX18TA-10960C017); World Bank for Climate-Smart Agriculture Investment Plans (CSAIPs) (CIAT: C-109-19); EU-IFAD under the CCAFS-IFAD project Increasing food security and farming system resilience in East Africa through wide-scale adoption of climate-smart agricultural practices (CIAT: C-082-14); CCAFS Flagship on Low-Emissions Development (FP3); Center for International Forestry Research’s Evidence-based Forestry (CIFOR-EBF)